1990
DOI: 10.1149/1.2086793
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Carbon Composite Electrodes from Fiber Precursors: II . Electrochemical Characterization of Stainless Steel‐Carbon Structures

Abstract: In this study, the capacitances of stainless steel-carbon composite electrodes in 1.0M Na2SO4 were determined as a function of stainless steel loading, sintering temperature, and sintering time (i.e., O. 1-0.5g of stainless steel fiber/lg of carbon fiber, 1323-1423 K, and 2.5-152 min, respectively). Kinetic parameters were determined for stainless steel sintering and catalytic carbon gasification by weight loss measurements and capacitance changes using ac impedance, single potential step methods, and cyclic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…demonstrated that high performance, three dimensional, microfibrous electrodes can improve the performance of capacitors, batteries, hybrid power cells, and electrolysis electrodes in a variety of applications [2,3]. The goal of this research was to apply this technology to a chlorate cell's cathode and reduce the overpotential between 200 and 400…”
Section: Auburn University's Center For Microfibrous Materials Manufamentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that high performance, three dimensional, microfibrous electrodes can improve the performance of capacitors, batteries, hybrid power cells, and electrolysis electrodes in a variety of applications [2,3]. The goal of this research was to apply this technology to a chlorate cell's cathode and reduce the overpotential between 200 and 400…”
Section: Auburn University's Center For Microfibrous Materials Manufamentioning
confidence: 99%
“…The catholyte in chlor-alkali cells is 30 wt% NaOH, which is non-corrosive towards both nickel and stainless steel. Previous research projects have provided the Auburn University Center for Microfibrous Materials Manufacturing with considerable expertise in designing nickel microfibrous materials [2,3]. As a result, the catalytic activity of a composite microfibrous material towards hydrogen evolution was tested in a chlor-alkali cell before a chlorate cell.…”
Section: Catalytic Performance and Electrode Development In Sodium Chmentioning
confidence: 99%
“…For example, carbon particles can be combined with an organic polymer binder such as poly(vinylidene difluoride) (PVDF), poly(tetrafluoroethylene) (PTFE), or ethylene/propylene/diene polymer (EPDM) forming a conductive, porous composite electrode. [5][6][7] Carbon particles can also be embedded into a metallic support such as stainless steel, 8 and carbon aerogels have been used to fabricate high surface area electrodes. 9 The carbon particles used for these applications are typically about 1-10 µm in diameter and have a wide range of crystal structures and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon electrodes are widely used in electrochemical charge storage, energy generation, and catalysis. Various techniques have been developed for the synthesis of these electrodes. For example, carbon particles can be combined with an organic polymer binder such as poly(vinylidene difluoride) (PVDF), poly(tetrafluoroethylene) (PTFE), or ethylene/propylene/diene polymer (EPDM) forming a conductive, porous composite electrode. Carbon particles can also be embedded into a metallic support such as stainless steel, and carbon aerogels have been used to fabricate high surface area electrodes ,, Both low surface area graphite particles and high surface area carbons are used for the anode in lithium ion batteries .…”
Section: Introductionmentioning
confidence: 99%
“…Tatarchuk et al 13,14 recently have reported the development and preliminary characterization of a stainless steelcarbon composite electrode which combines the high surface area of activated carbon fibers with the high conductivity of stainless steel fibers into a self-supporting sintered network. The electrodes are highly permeable to liquids and gases and have excellent electrical conductivity.…”
mentioning
confidence: 99%